"Let there be light": the role of vitamin D in the immune response to vaccines. (2nd November 2015) - Sadarangani, Sapna P; Whitaker, Jennifer A; Poland, Gregory A
Abstract : Vitamin D's non-skeletal actions, including immunomodulatory role, have been increasingly recognized. Of significance, many immune cells are able to synthesize a biologically active form of vitamin D from circulating 25-hydroxyvitamin D with subsequent intracrine actions, and the vitamin D receptor is broadly distributed. In this review, we discuss vitamin D's potent role in innate and adaptive immune responses and published studies evaluating the impact of serum vitamin D, vitamin D gene pathway polymorphisms or empiric vitamin D supplementation on vaccine immunogenicity. We highlight existing knowledge gaps and propose the steps needed to advance the science and answer the question of whether vitamin D may prove valuable as a vaccine adjuvant for certain vaccines against infectious diseases.